PenggunaanTepung Kulit Pisang dalam Ransum terhadap Kadar Kolesterol, Vitamin A, Profil Asam Lemak Kuning Telur Ayam Arab: The Effect of Banana Peel Meal usage in the Chicken Diet on Cholesterol, Vitamine A and Fatty Acid Profile of Arabian Chicken Egg Yolks - dwi margi suci; Rika Zahera; Mutia Sari; Widya Hermana (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2020)
The aim of this research was to measure the effect of yellow corn substitution with banana peel meal as a beta-carotene and antioxidant source in the chicken diet on cholesterol, vitamin A and fatty acid profiles of egg yolk Arab chicken. The experimental design used was a completely randomized design. Data were analyzed by Analysis of Variance (ANOVA) and significant differences between the treatments were analyzed by Duncan's Multiple Range Test. Eighty pullet of Arabic chickens (19 weeks old) were randomly assigned to four treatment diets with four replications for 6 weeks of fed trials. Dietary treatments consisted of R0 (0%) banana peel meal (TP) : 50% yellow corn (JK) and 3 levels of yellow corn and banana peel. The composition of yellow corn and banana peel meal used R1 (20 % TP ; 30% JK), R2 (30% TP : 20% JG) and R3 (40% TP :10% JG). The variables observed were production performance, cholesterol, vitamin A and fatty acid profile of the egg yolk. The results showed that egg yolk cholesterol levels were not significantly different compared to the control. Substitution of yellow corn with banana peel meal had increased vitamin A level up to 49% compared to the control. There was no difference in fatty acid profiles in all treatments observed. It is concluded that banana peel meal can be used to substitute 40 % of yellow corn in the chicken diet and tend to increased vitamin A of egg yolk. Key words: Arabic chicken, banana peel meal, cholesterol, fatty acid, yolk DAFTAR PUSTAKA Abel FAS, Adeyemi OA, Oluwole OB, Oladunmoye OO, Ayo-Ajasa OY, Anuoluwatelemi JO. 2015. Effect of treated banana peel meal on the feed efficiency, digestibility and cost effectiveness of broiler chicken diet. Journal of Veterinery Science & Animal Husbandry. 3 (1): 1-6 Abou-Arab AA, Abu-Salem FM. 2017. Nutritional and anti-Nutritional composition of banana peels as influenced by microwave drying methods. International Scholarly and Scientific Research & Innovation. 11(12): 845-852 Amrullah, IK. 2004. Nutrisi Ayam Petelur. Cetakan ke-3. Bogor (ID): Lembaga Satu Gunungbudi. Anhwange BA, Ugye TJ, Nyiaatagher TD. 2009. Chemical composition of Musa sapientum (Banana) peels. Electronic Journal of Environment, Agricultural and Food Chemistry. 8 (6):437-442 Antruejo A, Azcona JO, Garcia PT, Gallinger C, Rosmini M, Ayerza R, Coates W, Perez CD. 2011. Omega-3 enriched egg production: The effect of α-linolenic ῳ-3 fatty acid sources on laying hen performance and yolk lipid content and fatty acid composition. British Poultry Science. 52(6): 750-760 Aryani T, Mu’awanah IAU, Wydiantara AB. 2018. Karakteristik fisik, kandungan gizi tepung kulit pisang dan perbandingannya terhadap syarat mutu tepung terigu. Jurnal Riset Sains dan Teknologi. 2(2): 45-50 Arora A, Choudhary D, Agarwal G, Singh VP. 2008. Composition variation in β-carotene content, carbohydrate and antioxidant enzymes in selected banana cultivar. International journal of Food Science and Technology. 43: 1913-1921 Blandon JC, Hamady GAA, Abdel-Moneim A. 2015. The effect of partial replacement of yellow corn by banana peels with and without enzymes on broiler’s performance and blood parameters. Journal of Animal and Poultry Science. 4(1): 10-19 Diana, FM. 2013. Omega 6. Jurnal Kesehatan Masyarakat. 7(1): 26-31 Diarra SS. 2018. Peel meals as a feed ingredient in poultry diets. Chemical composition, dietary recommendation and prospect. Journal of Animal Physiology and Animal Nutrition. 102: 1284-1295 Chueh CC, Lin LJ, Lin WC, Huang SH, Jan MS, Chang SC, Chung WS, Lee TT. 2019. Antioxidant capacity of banana peels and its modulation of Nrf2-ARE associated gene expression in broiler chickens. Italian Journal of Animal Science. 18 (1): 1394-1403 Haryanto, A, Miharja K, Wijayani N. 2016. Effect of banana meal on the feed conversion ratio and blood lipid profile of broiler chickens. International Journal of Poultry Science. 15 (1) : 27-34 Has, H, Napirah A, Dewi L. 2017. Efektivitas substitusi kulit pisang dengan dedak padi dalam ransum ayam kampung. Makasar (ID): Seminar Nasional Peternakan. Universitas Hasanudin. Indra GK, Achmanu, Nurgiatiningsih A. 2013. Performans produksi ayam Arab (Gallus turcicus) berdasarkan warna bulu. Jurnal Ternak Tropika. 14 (1): 8-14 Konieczka M, Czauderna S, Smulikowsk S. 2017. The enrichment of chicken meat with omega-3 fatty acid by dietary fish oil or its mixture with rapeseed or flaxseed-effect of feeding duration dietary fish oil, flaxseed, and repeseed and n-3 enriched broiler meat. Animal Feed Science and Technology. 223 : 42-52 McDowell, L.R. 2000. Vitamine in Animal and Human Nutrition. 2nd Edition. Iowa (US): State University Press, Iowa. Mulyadi Y. 2013. Penggunaan pakan fungsional terhadap performan produksi dan kualitas telur ayam arab. Jurnal Ilmu Ternak. 13 (2): 27-33 [NRC] National Research Council. 1994. Nutrient Requirements of Poultry. 9th Revised Edition. Washington. D. C. (US) : National Academy Press, Nuraini, Sabrina, Latif SA. 2008. Performa ayam dan kualitas telur yang menggunakan ransum mengandung onggok fermentasi dengan Neurospora crassa. Media Peternakan. 31:195-202. Pereira A, Maraschin M. 2015. Banana (Musa spp) from peel to pulp: ethnopharmacology, source of bioactive compounds and its relevance for human health. Jurnal Ethnopharmacology. 160:149–163 Piliang WG, Djojosoebagio S. 2006. Fisiologi Nutrisi. Volume I. Edisi ke-2. Bogor (ID): IPB Press Rehaul-Godbert, S, Guyot N, Nys Y. 2019. The Golden Egg: Nutritional value, bioactivities, and emerging benefits for human health. Nutrients. 11: 1-26 (www.mdpi.com/journal/nutrient) Sartika RAD. 2008. Pengaruh asam lemak jenuh, tidak jenuh dan asam lemak trans terhadap kesehatan. Jurnal Kesehatan Masyarakat. 2(4): 154-160 Siregar HA, Rahmadi HY, Wening S, Suprianto E. 2018. Komposisi asam lemak dan karoten kelapa sawit Elaeis oleifera, interspesifik hibrida, dan Pseudo-backcross pertama di Sumatera Utara, Indonesia. Jurnal Penelitian Kelapa Sawit. 26 (2): 91-101 Suci DM, Fitria Z, Mutia R. 2017. Meat fatty acid and cholesterol content of native Indonesian Muscovy Duck Fed with rice bran in tradisional farm. Animal Production. 19 (1):37-45 Sutama, INS. 2008. Daun pepaya dalam ransum menurunkan kolesterol pada serum dan telur ayam. Jurnal Veteriner. 9: 152-156. Wiradimadja R, Burhanuddin H, & Saefulhadjar D. 2010. Peningkatan kadar vitamin A pada telur ayam melalui penggunaan daun katuk (Sauropus androgynus L. Merr) dalam Ransum. Jurnal Ilmu Ternak. 10 (2): 90-94